Pola bakteri resisten antibiotic dari sungai yang bermuara di Teluk Manado - Monica Maria Wantah; Henry Malcom Frank Palandeng; Frelly Valentino Kuhon (UNIVERSITAS SAM RATULANGI, 2026)
Background: Antibiotic Resistance is an increasing global issue that recently been found in the aquatic environment, including rivers. Rivers that flow through a dense population are most likely carrying domestic waste, livestock residues and healthcare effluents containing bacterias as well as antibiotic residue. Such condition urges antibiotic resistence which will somehow transport to the coastal ecosystem. Manado Bay, which receives water flow from multiple rivers, is at risk of accumulating resistant bacterial populations. Aim: To identify the presence and resistance patterns of bacteria in river water samples discharging into Manado Bay. Methods: A quantitative descriptive study was conducted at two river locations. Bacteria were identified using Gram staining, catalase, and coagulase tests. Antibiotic susceptibility testing used the Kirby-Bauer disk diffusion method following CLSI 2021 standards. Results: Four bacterial species were identified, which are Escherichia coli, Staphylococcus sp., Staphylococcus aureus, and Lactobacillus sp., each of which exhibited different resistance patterns to various types of antibiotics at each sampling location. Conclusion: Rivers flowing into Manado Bay contain antibiotic-resistant bacteria, indicating environmental exposure to antibiotic residues. These rivers may serve as pathways for the spread of resistant bacteria to coastal areas.